Nutritional Composition and Biological Activities of Donkey Milk: A Narrative Review - Qingyu Xu; Lin Wei; Xiuwen Chen; Hongzhen Zhu; Jinjin Wei; Mingxia Zhu; Muhammad Zahoor Khan; Changfa Wang; Zhenwei Zhang (Foods, 2025)
Donkey milk has received increasing attention in recent years due to its unique nutritional composition and potential biological activities. This comprehensive review analyzed the main nutritional components of donkey milk, including proteins, lipids, carbohydrates, vitamins, and minerals, while also examining its significant biological activities such as antioxidant, antimicrobial, immunomodulatory, and anti-inflammatory properties. The protein profile of donkey milk is notable for its high proportion of whey proteins (55–65%), resembling human milk more closely than cow milk. Its relatively low-fat content (approximately 1.29%) with higher proportions of unsaturated fatty acids provides nutritional advantages for specific dietary needs. The carbohydrate content, primarily lactose, contributes to energy provision and calcium absorption. Donkey milk is also distinguished by its rich vitamin profile, particularly vitamin C (about 4.75 times higher than cow milk), and essential minerals including calcium, phosphorus, and zinc. The biological activities of donkey milk extend to various applications in infant nutrition, particularly for children with cow milk protein allergies, potential medical treatments for infections and inflammatory conditions, and cosmetic formulations. Despite these promising attributes, the donkey milk industry faces challenges including low milk yield, lack of standardized production methods, and quality control measures. The sustainable development of the donkey milk industry requires comprehensive approaches to resource protection, technological innovation, brand building, and supportive policies to realize its full potential in contributing to human health and economic development.